1998
DOI: 10.1242/jeb.201.15.2287
|View full text |Cite
|
Sign up to set email alerts
|

Stress/Strain Behaviour of the Equine Laminar Junction

Abstract: The equine laminar junction plays a vital role in transferring the forces of weight-bearing between the epidermal hoof wall and the bone of the third phalanx, but the way in which it performs this function is poorly understood. Using samples from sites varying proximodistally and circumferentially around the hoof, the stress/strain behaviour of this tissue was characterised in three directions: radial tension and proximodistal and mediolateral shear. The influences of toe angle and length were also examined. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Given that our data argue against the sterile bed theory, it allows the hypothesis that the laminar interface of the normal horse' s foot is capable of reacting to load and disease. 12,13 Intuitively, variations in the magnitude, directions, and duration of applied load to the laminar interface can result in architectural changes similar to changes in skin stratum corneum thickness following changes in load. The ability of the interface to adapt to applied loads potentially contributes to the observation in our study that most of the measured variables differed among horses as well as from the proximal to distal position.…”
Section: Discussionmentioning
confidence: 99%
“…Given that our data argue against the sterile bed theory, it allows the hypothesis that the laminar interface of the normal horse' s foot is capable of reacting to load and disease. 12,13 Intuitively, variations in the magnitude, directions, and duration of applied load to the laminar interface can result in architectural changes similar to changes in skin stratum corneum thickness following changes in load. The ability of the interface to adapt to applied loads potentially contributes to the observation in our study that most of the measured variables differed among horses as well as from the proximal to distal position.…”
Section: Discussionmentioning
confidence: 99%
“…level of the hoof wall. The basic anatomic features of the laminar junction have been described, 3,4,a as have the material properties of the laminar junction 5,6 and the relationship between internal and external features of the hoof wall. 7 A better understanding of the form and function of the laminar junction may aid practitioners in diagnosing and treating hoof disease.…”
mentioning
confidence: 99%
“…23 Given the lateral location of the forelimb in relation to the center of a horse' s body, more loading could be expected at the medial quarter and toe. 24 Assuming that both sides of a hoof are morphologically similar and have similar elasticity, 25,26 the higher strains observed on the lateral side of the horses' hooves in the present study suggest that different forces act on each side. However, medial and lateral angles also affect strains in the hoof wall, with decreasing compression as the angle increases, particularly at the lateral side.…”
Section: Discussionmentioning
confidence: 58%
“…Other factors to be considered are the exercise history and the individual stride characteristics of each horse, which might affect the stiffness of the hoof wall and hence its mechanical behavior. 26 Unfortunately, detailed exercise history of the horses in the study reported here could not be obtained.…”
Section: Discussionmentioning
confidence: 97%